Assessing 3D metric data of digital surface models for extracting archaeological data from archive stereo-aerial photographs. (August 2016) - Papworth, Heather; Ford, Andrew; Welham, Kate; Thackray, David
Abstract: Archaeological remains are under increasing threat of attrition from natural processes and the continued mechanisation of anthropogenic activities. This research analyses the ability of digital photogrammetry software to reconstruct extant, damaged, and destroyed archaeological earthworks from archive stereo-aerial photographs. Case studies of Flower's Barrow and Eggardon hillforts, both situated in Dorset, UK, are examined using a range of imagery dating from the 1940s to 2010. Specialist photogrammetric software SocetGXP ® is used to extract digital surface models, and the results compared with airborne and terrestrial laser scanning data to assess their accuracy. Global summary statistics and spatial autocorrelation techniques are used to examine error scales and distributions. Extracted earthwork profiles are compared to both current and historical surveys of each study site. The results demonstrate that metric information relating to earthwork form can be successfully obtained from archival photography. In some instances, these data out-perform airborne laser scanning in the provision of digital surface models with minimal error. The role of archival photography in regaining metric data from upstanding archaeology and the consequent place for this approach to impact heritage management strategies is demonstrated. Highlights: Reconstructing earthworks is possible using archive stereo-aerial photographs. DSM from archive photographs are comparable with airborne laser scanning. Rigorous statistical comparisons with established geomatic techniques.